Hydrogen adsorption capacity reduction of activated carbon produced from Indonesia low rank coal by pelletizing - Sri Harjanto,; Latifa N. Noviana,; Mia Diniati,; Stefanno W. Yunior,; Nasruddin, (Universiti Kebangsaan Malaysia, 2015)
Coal-based activated carbon materials is a prospective materials for hydrogen storage application. The present work aimed to study the effect of post treatments including mechanical milling process and pelletization and simulating experimentally the conditions of pelletization of fine particles of activated coal. Post treatment of activated coal consist of 2 steps mechanical milling process in planetary ball mill followed by pelletization. First step of mechanical milling process gave particle size reduction and second step was undertaken to maintain activity of activated coal. Second step of mechanochemical process were done in dry (ACP-A) and wet condition (ACP-B) with the ratio of sample: KOH was 1:1 and performed for 1 h. Then they will be formed into pellets with the addition of binder which contained fructose, glucose and oligo. Some examinations such as PSA, BET, SEM and XRD were performed to determine the characteristics of activated carbon materials including hydrogen adsorption capacity testing. Particle size reduction of activated carbon reached 98.9% after planetary ball milling. The raw material of activated carbon (AC) has hydrogen adsorption as much as from 0.30 and 0.25 wt. % from -5 and 25oC measurements, respectively. As predicted the adsorption of hydrogen gas of pelletized activated carbon from bituminous coal decreased due to post treatment process about 47% for ACP-A and 60% for ACP-B at 4000 Bar.